GEJALA PERGAULAN PEMUDA DITINJAU SESUAI NILAI DAN MORAL YANG BERLAKU DI MASYARAKAT BUKIT PANYANDAAN, DESA MANDALA MEKAR, KABUPATEN BANDUNG, JAWA BARAT - Moechamad Rafi Idzwan Maulana Al-Farisi; Matnur Ritonga (Bajang Institute, 2023)
Adolescence is a period when an individual experiences a transition from one stage to the next or commonly referred to as development. But these development are always monitored by their parents so that they develop in a positive direction or without extra parental guidance or monitoring so that they develop in a negative direction and experience changes in their emotions, interests, bodies, bahavior patterns, and are also full of problems. Critical thingking culture is the power of human mind or common sense to judge whether or not a source of news or information is valid, distinguish what is relevant and what is not, distinguish what is fact and what is not, or the power of reason to analyze existing facts. Motivation is an energy change in a person’s personality which is characterized by the emergence of affective (feelings) and reactions to achieve a goal. The purpose of this study was to determine how the influence of promiscuity on critical culture and motivation for community education in Mandala Mekar Village, Cimeunyan District, Bandung Regency. In order to know the extent of the influence of the promiscuity. Develop in a positive direction or the opposite direction is negative.